Do Combined Pharmacist and Prescriber Efforts on Medication Reconciliation Reduce Postdischarge Patient Emergency Department Visits and Hospital Readmissions?. Issue 3 (4th October 2017) - Baker, Michelle; Bell, Chaim M.; Xiong, Wei; Etchells, Edward; Rossos, Peter G.; Shojania, Kaveh G.; Lane, Kelly; Tripp, Tim; Lam, Mary; Tiwana, Kimindra; Leong, Derek; Wong, Gary; et al.
Abstract : BACKGROUND: Although medication reconciliation (Med Rec) has demonstrated a reduction in potential adverse drug events, its effect on hospital readmissions remains inconclusive. OBJECTIVE: To evaluate the impact of an interprofessional Med Rec bundle from admission to discharge on patient emergency department visits and hospital readmissions (hospital visits). METHODS: The design was a retrospective, cohort study. Patients discharged from general internal medicine over a 57‐month interval were identified through administrative databases. Patients who received an enhanced, Gold level, Med Rec bundle (including both admission Med Rec and interprofessional pharmacist‐prescriber collaboration on discharge Med Rec) were assigned to the intervention group. Patients who received partial Med Rec services, Silver and Bronze level, comprised the control group. The primary outcome was hospital visits within 30 days of discharge. RESULTS: Over a 57‐month period, 9931 unique patient visits (n = 8678 patients) met the study criteria. The main analysis did not detect a difference in 30‐day hospital visits between the intervention (Gold level bundle) and control (21.25% vs 19.26%; adjusted odds ratio, 1.06; 95% confidence interval [CI], 0.95‐1.19). Propensity score adjustment also did not detect an effect (16.7% vs18.9%; relative risk of readmission, 0.88; 95% CI, 0.59‐1.32). CONCLUSION: A long‐term, observational evaluation of interprofessional Med Rec did not detect a difference in 30‐day postdischarge patient hospital visits between patients who received enhanced versus partial Med Rec patient care bundles. In future prospective studies, researchers could focus on evaluating high‐risk populations and specific elements of Med Rec services on avoidable, medication‐related hospital admissions and postdischarge adverse drug events.